Evaluating Pragmatic Competence in Language Learners Through an Assessment of Current Measurement Tools - Paluanova, Khalifa (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2024)
This study reviews and evaluates current tools used to measure pragmatic competence in language learners. Pragmatic competence—the ability to use language appropriately in social contexts—is essential for effective communication in a second language. This article assesses various measurement tools, including discourse completion tests (DCTs), role-plays, self-assessment surveys, and technology-assisted assessments, analyzing their effectiveness and limitations. Findings suggest that each tool offers unique benefits, though a combination of traditional and digital methods provides the most comprehensive evaluation. The study concludes that blending these approaches allows for a more accurate assessment of pragmatic competence, supporting language educators in creating balanced evaluations for language learners.